Multidisciplinary management of intrahepatic cholangiocarcinoma: Current approaches. (June 2017) - Guro, Hanisah; Kim, Jin Won; Choi, YoungRok; Cho, Jai Young; Yoon, Yoo-Seok; Han, Ho-Seong
Abstract: Intrahepatic cholangiocarcinoma (ICC) is a common primary hepatic tumor. However, its outcomes are usually worse than those of hepatocellular carcinoma owing to its non-specific presentation and detection at an advanced stage. The most widely used serum marker, carbohydrate antigen 19-9, is non-specific. Furthermore, imaging studies rarely identify any pathognomonic features. Surgery is the only treatment option that offers a chance of long-term survival. However, the resectability rate is low owing to the high frequencies of intrahepatic metastases, peritoneal carcinomatosis, or extrahepatic metastases. Surgical treatment should be tailored according to the macroscopic classification of ICC (e.g. mass-forming, periductal infiltrating, and intraductal growth types) because it reflects the tumor's dissemination pattern. Although lymph node metastasis is a negative prognostic factor, the importance and extent of lymph node dissection is still controversial. To improve patient survival, liver transplantation is considered in some patients with unresectable ICC, especially in those with an insufficient remnant liver volume. Minimally invasive procedures, including laparoscopic and robotic liver resection, have been tested and achieved comparable outcomes to conventional surgery in preliminary studies. No randomized trials have confirmed the efficacy of adjuvant chemotherapy in ICC, and several trials have evaluated molecular-targeted agents as monotherapy or in combination with cytotoxic chemotherapy. Multidisciplinary approaches are necessary to improve the outcomes of ICC.